Editorial - Diaz Dumont, Jorge Rafael (2023)
The National Autonomous University of Tayacaja Daniel Hernández Morillo, presents Vol. 6 No. 1 (2023) of the TAYACAJA Scientific Research Journal, which is an indexed scientific publication, edited by the Research Vice Presidency and is oriented to the publication of scientific articles originals, in the specialty of "Forestry Sciences and Agricultural Sciences", according to the indicated norms. The TAYACAJA Scientific Research Journal is a publication that has ISO 9001-2015 certification, is refereed and has ISSNe: 2617-9156. It is indexed to: LATINDEX (Catalog 2.0), REDIB, CROSSREF, OCLC WORLD CAT, GOOGLE SCHOLAR, ROAD, LATIN REV, ALICIA, LA REFERENCE, MIAR, AURA, OPEN AIRE, BASE, EZ3, ERIH PLUS. Likewise, each of the published articles has a DOI.